Strategic Role of University in Creating Young Entrepreneur - Rosyadi, Imron; Mardalis, Ahmad; Iqbal Fasa, Muhammad; Suharto, Suharto (Opción, 2019)
This research aims to develop a partnership model between colleges and stake- holders as an effort to create young entrepreneurs. Research settings conduct- ed in selected colleges are: University of Sebelas Maret (UNS), Institute of Agama Islam Negeri (IAIN) Surakarta and University of Muhammadiyah Surakarta (UMS). This research used primary data that obtained through field observation techniques, focus group discussion (FGD) and an in depth interview for the college stakeholders who are considered as key figures in the student affairs. The method of analysis used was a descriptive-analyti- cal approach. The results of this research showed that there are a number of strategic roles in developing college partnership models and stakeholders that include: (1) formulate a business development strategy: (i) entrepreneur- ial teaching and management business based on soft skill and (ii) organizing intensive, systematic and unified education and training on business manage- ment and entrepreneurship digital economy based; (2) universities synergized with bank and HIPMI for the purpose of evaluation of Business plan, business assistance and business consultant for business students; (3) Provide the ease of access to capital for business students whose business plan is assessed wor- thy by the team of the assessment.